AN OVERVIEW OF BREAKFAST PATTERNS AND LIFESTYLES ASSOCIATED WITH BODY MASS INDEX IN MALAYSIA - Noorul Faiza Binti Mohamed Bharuddin; Ezza Fazlen (Universitas Airlangga, 2020)
Background: Over the past two decades, a high body mass index (BMI) has become the world's largest public health concern. There have been numerous studies suggesting that breakfast patterns and lifestyle choices are associated with an individual's BMI. Purpose: This research aims to describe the distribution of breakfast patterns and lifestyle choices according to BMI in Shah Alam, Malaysia. Method: This is a descriptive study with a cross-sectional design. The respondents in this study are people who live in Shah Alam, Malaysia, and are between the ages of 18 and 35 years old. The instrument used is a questionnaire. Results: The data shows that the majority of respondents who were obese (28.24%) were non-smokers (14.62%), never drank alcohol (15.95%), had not exercised in the past two weeks (17.28%), slept six to eight hours per day (17.28%), and had a pattern of skipping breakfast (23.92%). On other hand, the majority of respondents who were in the normal BMI range (34.55%) were non-smokers (29.57%), never drank alcohol (30.56%), slept six to eight hours per day (18.94%), and had a pattern of eating breakfast (20.60%). Conclusion: Obesity is more common in people who skip breakfast, as weight gain occurs because of unhealthy food choices made to replace breakfast. An unhealthy lifestyle also contributes to a high BMI, including smoking, alcohol consumption, and a sedentary lifestyle.